Functional promoter polymorphism in the VKORC1 gene is no major genetic determinant for coronary heart disease in Northern Germans - Watzka, Matthias; Nebel, Almut; Eddine El Mokhtari, Nour; Ivandic, Boris; Müller, Jens; Schreiber, Stefan; Oldenburg, Johannes (Thrombosis and Haemostasis, 2007)
Recently, the C-allele of polymorphism rs2359612 (VKORC1: c.283+837C>T) in the VKORC1 gene has been reported to represent a major risk factor for coronary heart disease (CHD), stroke, and aortic dissection in Chinese patients. VKOR activity itself is the rate-limiting step in gamma-carboxylation of vitamin K-dependent coagulation factors (factors II, VII, IX, X, protein C, S, and Z) and proteins of calcium metabolism (matrix Gla protein and osteocalcin). Gamma-carboxylation is essential for the biological activity of these proteins that have been previously hypothesised to play a role in the pathogenesis of atherosclerosis. It was the objective of this study to analyse the VKORC1 genotype frequency in patients with CHD and controls from Northern Germany and to investigate the association of VKORC1 and CHD risk in patients with an European background. CHD paients (n = 901) and healthy controls (n = 521) were part of the PopGen biobank. Case and control samples were matched for ethnic and geographic origin, age and gender. After typing German CHD patients and control individuals, no evidence for a statistically significant association was detected between VKORC1 genotype and CHD phenotype. Also stratification for gender and myocardial infarction yielded no significant results. In conclusion, the discrepant association findings in Chinese and German populations may be explained by ethnic differences in genetic and perhaps environmental predisposition, modifying the polygenic CHD phenotype by interacting withVKORC1 variants and thus conferring disease susceptibility in some populations, but not in others.
Keywords: Coronary heart disease; haplotype; rs9923231; vitamin K; VKORC1